Effectiveness of Photodynamic Therapy as Antiseptic Measure for Oral Cavity and Pharynx: A Systematic Review - Diana Sologova; Marina Petukhova; Polina Podoplelova; Dinislam Davletshin; Anna Firsova; Andrey Grishin; Mikhail Grin; Nikita Suvorov; Yuriy Vasil'ev; Sergey Dydykin; Elena Rysanova; Victoria Shchelkova; et al. (MDPI AG, 2023)
Background: The complex traditional treatment of inflammation diseases in oral cavity includes the prescription of antibiotic and antiseptic therapy. This systematic review aims to evaluate the effect of photodynamic therapy as a part of management of inflammatory diseases in oral cavity; Methods: The study is presented in accordance with the preferred reporting points for systematic reviews and meta-analyses (PRISMA). This systematic review was conducted using electronic databases such as Medline PubMed, Scopus and the Cochrane Central Register of Controlled Trials. All the studies in this systematic review, were randomized, the risk of bias 2 (ROB 2) were assessed; Results: Considering the inclusion and exclusion criteria, we included 10 randomized clinical trials, published up to 2023 investigating the application of photodynamic therapy as a part of management of inflammatory diseases in oral cavity. The diode laser was used in the oral cavity in the zone of inflammatory process (gingivitis, mucositis, periimplantitis, marginal periodontitis, abscess, periostitis, osteomyelitis etc.) in nine studies or in the zone before surgical procedures in one study; Conclusion: Based on the results of clinical studies, it can be stated that photodynamic therapy shows good results for operations performed in the oral cavity and pharynx.